Efficacy of surgical microwave ablation for recurrent hepatocellular carcinoma after curative hepatectomy. Issue 3 (March 2020) - Ryu, Tomoki; Takami, Yuko; Wada, Yoshiyuki; Hara, Takanobu; Sasaki, Shin; Saitsu, Hideki
Abstract: Background: Little evidence exists regarding postrecurrence survival after microwave ablation for recurrent hepatocellular carcinoma (HCC) after curative hepatectomy; we aimed to evaluate the feasibility of surgical microwave ablation. Methods: In this retrospective review, we enrolled patients who underwent curative hepatectomy for primary HCC in our department and had intrahepatic recurrence. We analyzed overall survival according to treatment modality to clarify the prognostic factors for survival. Results: Of 257 patients, 119 had intrahepatic recurrence. Three patients underwent repeat hepatectomy; 75 patients underwent surgical microwave ablation, and 34 patients underwent transcatheter arterial chemoembolization or hepatic arterial infusion chemotherapy. The median postrecurrence survival time and 5-year postrecurrence survival after surgical microwave ablation were 37.4 months and 55.4%, respectively. The major complication rate (Clavien–Dindo classification IIIa or above) after surgical microwave ablation was 5.3% with no mortality. Multivariate analysis showed that microvascular invasion at primary tumors, and recurrent tumors within 3 cm and 3 nodules were independent prognostic factors for overall survival after surgical microwave ablation for recurrent HCC. Conclusion: Our results suggested that surgical microwave ablation is safe and feasible for recurrent intrahepatic HCC after curative hepatectomy. Close follow-up and further curative treatment could be important for improving postrecurrence survival.